Navigating forced migration in the EU: challenges for families with disabled children affected by the Russo-Ukrainian war - Olha Stoliaryk; Tetyana Semigina (Eastern Journal of European Studies)
This paper examines the challenges faced by migrant families raising children with disabilities during the Russo-Ukrainian War and subsequent mass migration to European Union countries. Drawing on critical refugee studies, critical disability studies, and resilience theory, the study explores the intersecting factors influencing their experiences. Findings from interviews with 30 respondents relocated to 6 countries (the Czech Republic, Germany, France, Hungary, Italy, and Poland) reveal significant barriers to accessing essential services, navigating bureaucratic processes, and adapting to new environments. Despite these challenges, families exhibit remarkable resilience and resourcefulness. Recommendations include enhancing support systems, promoting dialogue and collaboration among stakeholders, and defining mechanisms for responsibility sharing among EU countries. The study underscores the urgent need for inclusive policies and robust support structures to address the unique needs of migrant families raising children with disabilities in forced migration contexts.